Cross-Culturally Modified University of Pennsylvania Smell Identification Test for a Turkish Population. Issue 5 (September 2015) - Altundag, Aytug; Tekeli, Hakan; Salihoglu, Murat; Cayonu, Melih; Yasar, Halit; Kendirli, Mustafa T.; Saglam, Omer
Background: The University of Pennsylvania Smell Identification Test (UPSIT) is a well-developed and popular olfactory test, which has been validated in various populations. However, there was only one study in a Turkish population, and this study indicated that the North American version of the UPSIT was not enough to evaluate the olfactory functions of Turkish population. So, we developed a cross-cultural adaptation of the UPSIT, the UPSIT-Turkish (UPSIT-T). Thus, the goal of this study was to investigate the applicability of the UPSIT-T in healthy Turkish subjects. Material and Methods: The study included 51 healthy individuals who reported having normal olfactory function. The participants were administered the North American version of the UPSIT firstly, and then, after a day UPSIT-T was applied to the participants. The results of two smell tests were compared, and the applicability of UPSIT-T was evaluated. Results: The mean (standard deviation) value for correctly identified odors was 27.2 ± 5.7 (range, 14–38) with the UPSIT application, whereas the mean (standard deviation) value for correctly identified odors was 35.9 ± 3.1 for UPSIT-T. There was a statistically significant increase in the scores of the participants when UPSIT-T was performed (p < 0.001). The identification rates of 10 test odorants were <80% for our study group, and 2 of 10 were <70% for the UPSIT-T. Conclusion: The UPSIT-T modification is an adequate olfactory test for clinical use in a Turkish population.